2010
DOI: 10.1159/000303530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Surgical Modalities in Recurrent or Persistent Trigeminal Neuralgia

Abstract: Background/Aims: In recurrent or persistent idiopathic trigeminal neuralgia (TN) after initial operation, additional surgical procedures may be required. There are numerous articles reporting the outcomes of additional surgical treatment and it is unclear how best to treat patients with recurrent or persistent TN. We evaluated the subsequent therapeutic options for recurrent or persistent TN. Methods: The study was a retrospective study. The authors reviewed 29 patients (15 female/14 male) who underwent retrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Han et al [13] reported that MVD may be used as an effective alternative for patients with a history of failed percutaneous procedures. We also believe that other surgical procedures may be used as an effective alternative for patients resistant to PRT.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [13] reported that MVD may be used as an effective alternative for patients with a history of failed percutaneous procedures. We also believe that other surgical procedures may be used as an effective alternative for patients resistant to PRT.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common disorder having great impact on the quality of life of patients (Yoshino et al, 2003;Han et al, 2010). Besides medication and interventional procedures, radiofrequency thermocoagulation (RFT) is one of the most important surgical approaches extensively applied in the treatment of TN.…”
Section: Introductionmentioning
confidence: 99%
“…In these instances, recurrence can be prevented. Although the success rate of re-operation was lower than that of the initial operation, performing a second surgery showed a higher long-term success rate than did other treatment modalities1630). There was a higher risk of facial dysesthesia after a second surgery than after the first surgery.…”
Section: Discussionmentioning
confidence: 86%